Beet Productivity and Quality, Considering the Application of Nitrogen Doses - Claudiane Reiz Barreto; Márcio Roggia Zanuzo; Carmem Wobeto; Claudineli Cássia Bueno da Rosa (Revista Brasileira Multidisciplinar - ReBraM /Brazilian Multidisciplinay Journal, 2013)
The beet is among the main vegetables grown in Brazil occupying the 13th position in terms of economic value of its production and nitrogen fertilization has a fundamental role in the quality and in the productivity of the culture. The present study evaluated the influence of nitrogen doses (0, 25, 50, 75, 100 and 150 kg ha-1) in coverage way in the Early Wonder and Itapuã beet cultivars. The experimental design was a randomized block design in a factorial scheme 2x6 (cultivar x doses) with four replicates. The number of leaves, chlorophyll content, weight, diameter, total acidity, pH and soluble solids were evaluated. Only the number of leaves parameter varied significantly according to the applied doses and varieties, obtaining more leaves in Itapuã at a dose of 25 kg ha-1. Considering the medium weight there was significant result only in the varieties in which the cultivar Itapuã was predominant also in the dose of 25 kg ha-1. The other sources of variation studied did not respond significantly to the doses and cultivars.